PREVALENCE OF NONALCOHOLIC - FATTY LIVER DISEASE IN METABOLIC SYNDROME - A HOSPITAL-BASED CROSS-SECTIONAL STUDY - Kajaria, Divya (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: 21st century is dedicated to noncommunicable diseases; it may be diabetes, hypertension, obesity, or constellation of all known as metabolic syndrome. The main objective of this paper is to assess the prevalence of nonalcoholic fatty liver disease (NFLDS) in metabolic syndrome and its impact on the severity of metabolic syndrome in term of dyslipidemia, mean systolic pressure and body mass index (BMI). Methods: A cross-sectional study was conducted on 100 patients selected randomly during the period of January 2017-March 2017 from the outdoor patient department of Kayachikitsa of All India Institute of Ayurveda. Patient included on the basis of a screening pro forma based on the diagnostic criteria of metabolic syndrome on the basis of Third Adult Treatment Panel of the National Cholesterol Education Program criteria and 50 controls were included in the study. Pro forma also included general information regarding previous illness, socioeconomical status, BMI, evaluation of vital parameters, and lipid and thyroid profile, along with other routine laboratory parameters. Ultrasonography report is taken as the evidence for the diagnosis of fatty liver disease. Results: Frequency distributions and Chi-square statistics were used for categorical variables. Logistic regression analyses Students' t-test, Chi-square test, linear regression, and multiple logistic regression models were used for statistical analysis. p<0.05 was considered significant. BMI, waist circumference, mean systolic pressure, diastolic blood pressure, fasting blood sugar, triglycerides, total cholesterol, low-density lipoprotein (LDL) cholesterol were significantly higher, and high-density lipoprotein cholesterol, was significantly low in the study group compared to the control group. In the metabolic syndrome group, 67 patients (67%) had fatty liver Grade I, 34 had Grade II fatty liver (34%), 6 patients were having hepatomegaly with coarse echotexture (6%) and 4 patients were having cholelithiasis. NFLDS was significantly associated with metabolic syndrome group (p<0.0001). There was a significant linear association between fatty infiltration in liver and BMI, total cholesterol, triglycerides, and LDL cholesterol in the metabolic syndrome group in the linear regression model. Multiple logistic regression analysis recognized the association between fatty liver disease and BMI with dyslipidemia (p<0.001) in the metabolic syndrome group. Conclusion: It is concluded from this study that there is a significant association between NFLDS and metabolic syndrome, and it highlights the importance of evaluating liver profile in patients with metabolic syndrome.